Analysis Of Learning Environment In Islamic Integrated Science Learning In Madrasah Ibtidaiyah - ‘Azizah, Wida Nurul; Alvan Hazhari; Ridwan, Muhammad; Wahidah, Putri Nur (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
A conducive learning environment is crucial for supporting science education integrated with Islamic values at Madrasah Ibtidaiyah. This study aims to analyze the learning environment in these institutions, examining supporting and inhibiting factors in creating an ideal environment for Islamic-based science learning, as well as the roles of teachers, students, and educational facilities in shaping the learning environment. A literature study (library research) was employed as the research method. The findings indicate that the physical, social, and psychological environments at Madrasah Ibtidaiyah significantly contribute to the learning process. Key supporting factors include teacher competence, a flexible curriculum, the availability of teaching aids, and the integration of Islamic culture in the madrasa. However, challenges such as limited facilities, the lack of thematic teaching materials, and insufficient teacher training remain significant obstacles. The roles of teachers as facilitators, motivators, and learning designers, as well as the active participation of students, are essential for bridging science education with Islamic teachings. Additionally, supporting educational facilities such as mini laboratories, teaching aids, and Islamic-based teaching materials further enrich the learning experience. By addressing these challenges and optimizing supporting factors, it is anticipated that the learning environment at Madrasah Ibtidaiyah will not only enhance scientific understanding but also reinforce spiritual values. The conclusions offer recommendations for strategies to strengthen collaboration among teachers, students, and educational facilities in Islamic integrated science learning.